Geostandards and Geoanalytical Research Bibliographic Review 2020. Issue 1 (15th March 2022) - Weis, Ulrike; Stoll, Brigitte; Förster, Michael W.; Hell, Katharina; Kaiser, Viktoria; Otter, Laura M.; Jochum, Klaus Peter
Abstract : Key Points Literature review of 7200 geoanalytical publications for the year 2020. 628 selected articles with summaries of target analytes, relevant reference materials and producers. Selected publications include data obtained by new analytical developments and improved analytical protocols for established RMs, and identifies recently developed RMs for specific scientific topics.